Issue of the systemic teaching in biology (Journal of Educational Sciences, 2017)
In the article were the problems of the systemic teaching in biology discussed. The main task of education is the teaching of particular concepts using structural and systemic approaches. If to consider the biology as a discipline, according to the system-structural approach in biology teaching, for the content of the educational material and the methodological structure must meet certain requirements. As a result, students are formeddidactically optimal, favorable conditions for the development of systems thinking capabilities. «From the general to the particular» - one of the principles of the laws of individual development. In pedagogical practice, it is considered in the context of a systematic structural approach. The system consists from interconnected elements, each of which is the unevenness in the structure and the number of its components. The systems teaching in biology is the study of the basic levels of the life organization of variousorganisms. It is «backbone» of biological education, providing a logical sequenceand unity at all stages of the understanding of educational material. Development of systems thinking for students is a long process. It is therefore advisable in the study chapter «Plants», «Animals», «Human» in the early stages of learning to use a «model». In this article discusses the basic model for understanding the relationship of living organisms on the planet, which recommended for biology teaching with a systematic approach.
Keywords: systems of training of biology; training and education; didactics; training materials; metabolism; growth and development